Analisis Tindak Tutur Ilokusi Dalam Film Pendek “Capciptop! (2020)” Pada Kanal Youtube Ravacana Films (International Forum of Researchers and Lecturers, 2023)
This study aims to determine (1) the types of illocutionary speech acts in the short film